PROSES PERKEMBANGAN DESA WISATA DI KECAMATAN BASO KABUPATEN AGAM (Studi Kasus: Nagari Simarasok dan Nagari Padang Tarok) - suhendra, suhendra suhendra (JURNAL BUANA, 2026)
The development of tourist villages, especially natural tourism, is of course supported by the potential of the landscape with good management. In Baso District, Agam Regency, there are tourist village destinations, namely Nagari Simarasok Tourism Village and Nagari Padang Tarok Tourism Village. The aim of this research is to find out: 1) Landscape conditions, 2) Community involvement, 3) the development process of Nagari Simarasok and Nagari Padang Tarok as tourist villages in Baso District, Agam Regency. The method used is mixed methods with 8 informants. person. Data analysis uses geomorphological analysis by Van Zuidam (1985) to determine the condition of the landscape, the Tourism Area Life Cycle (TALC) theory by Richard Butler (1978) to determine the position of development of tourist villages and The POET model by Otis.D Duncan (1964) to determine involvement of the community. The results of the research are: 1) the landscape conditions of Nagari Simarasok contain volcanic land units at the foot of fluvial volcanic slopes, fluvial river channels, karst hills, karst dome hills and structural topography of hills to mountains with flow patterns related to layered rock outcrops, whereas in Nagari Padang Tarok contains volcanic land units at the foot of lower fluvial volcanic slopes, fluvial river channels, strong undulating structural topography to hills with flow patterns related to joints and faults and structural topography of hills to mountains with flow patterns related to layered rock outcrops. 2) Nagari Simarasok Tourism Village and Padang Tarok Tourism Village have involved the community in their development process. 3) Nagari Simarasok Tourism Village is at the development stage while Nagari Padang Tarok is at the involvement stage of its development.